Revealing Originality of Song Works: An Analysis to the Copyright Law - Larasati, Desrezka Gunti (Indonesia Law Review, 2014)
The topic of this paper is to describe the defining criteria of originality of song works. The aspect of originality is important to make such work be protected by Copyright Law. In this research, the criteria to define originality are based on certain doctrines and/or theories of originality that may vary case by case. The use of such doctrines and/or theories are necessary, since the stipulations regarding originality in the Indonesian Copyright Act has not been considered suffice. With regard to the song works, the criteria of originality may be different from other works. Therefore, a comprehensive research on the characteristics of song as a work is also important. This research is a qualitative research with prescriptive design. The research depicts the use of certain doctrines and/or theories as supplementary provisions to the Copyright Law in defining the originality of songs, which have specific characteristics resulted from their author’s creations and intellectuals.